ADAPTIVE CHANGES IN THE CARDIOVASCULAR SYSTEM AND OVERTRAINING SYNDROME RESULTING FROM EXCESSIVE PHYSICAL ACTIVITY - Zuzanna Kafara,; Dominika Jurczak,; Julia Koronczok-Matusiak,; Agnieszka Kafara,; Konrad Kulka,; Wiktoria Król,; Donata Kowalczyk,; Zuzanna Lechowska,; Katarzyna Michta,; Rafał Szarek, (International Journal of Innovative Technologies in Social Science, 2025)
Research objectives: Regular physical activity is widely recognized as a key component of a healthy lifestyle. While moderate effort brings numerous benefits, engaging in extreme physical activity introduces new challenges and risks. Intense exercise, despite its undeniable health benefits, can lead to unpredictable changes in the body. This paper identifies the possible adaptive changes of the cardiovascular system and the risk of developing overtraining syndrome as a result of long-term practice of intense exercise.Methods and key findings: Two medical textbooks, thirty-eight scientific articles published between 2010 and 2024, and one article from 2005 were reviewed, with findings indicating that regular high-intensity training can lead to myocardial hypertrophy, reduced resting heart rate, and a smaller increase in heart rate in response to submaximal effort. An increased risk of arrhythmias and myocardial fibrosis has been observed in competitive athletes. Prolonged excessive exercise can result in overtraining syndrome, which may present as persistent fatigue, muscle and joint discomfort, and mood disturbances, among other symptoms.Conclusions: The paper emphasizes the need to individualize training programs and proves the validity of regular monitoring of athletes' health.  It also highlights the necessity for further research into overtraining syndrome and the adaptation of the cardiovascular system to intense exercise. Particular attention was paid to the diagnostic difficulties associated with overtraining syndrome due to the subjectivity of symptoms and the limited number of clinical studies. The significance of an interdisciplinary approach in understanding the body's adaptation to overload was emphasized, considering physiological, biochemical, and psychological factors.